A Theoretical and Empirical Review of Development Planning in Pakistan: A Journey from Traditional Planning to Strategic Planning - Tagar, Hamzo Khan; Nazir, Hira; Tagar, Abdul Karim; Bijarani, Ghulam Ali (Advances in Social Sciences Research Journal, 2020)
The basic aim and object of the study to examine the institutional structure of development planning, and polices in Pakistan in the context of its impact on inclusive growth and in addition to develop a coherent road map in the context of regional and global development objectives of the modern world. The study addressed that present development planning set up in not addressing poverty and inequality at large due to its time-barred framework. The study recommended that the structural changes are needed in the present planning mechanism from district to province and planning commission/ from top to bottom. The capacity of development planners should be enhanced to formulate sustainable development policies to create a robust development planning system in the country. The study suggests continues reforms in development spending to reduce waste of available resources and its focus should be on regional and economic disparities as a policy shift a development for all. The institutional development planning should be focused to produce the required quality skilled human development force in the context of the lowest human development index in the region. There is an urgent need to adopt alternative development policies practices and strategic planning concepts followed by developed nations in the recent past as a way forward